Sosialisasi Pola Hidup Bersih Dan Sehat (PHBS) Di Mdt Al Hidayah Sumber Sari Kec Kabawetan Kab Kepahiang - Situmorang, Anggita; Fernandes, Brilian; Tantionika, Zella; Agustin, Melly; Murwati, Murwati; Azissah, Danur; Wulandari, Wulandari; Rohani, Tuti (Universitas Dehasen Bengkulu, 2025)
PHBS stands for clean and healthy living patterns or behaviors. More precisely, PHBS is a movement carried out by maintaining cleanliness and health of the body and the surrounding environment. Clean and healthy living behavior (PHBS) is a step that must be taken to achieve optimal health status for everyone. Objective: At the end of the counseling process, all children at MDT AL HIDAYAH Sumber Sari Village, Kebawetan Kec Kepahiang Kab, can understand and understand about Clean and Healthy Lifestyle (PHBS). Methods: The method used in this counseling is by delivering material using PPT and Video Animation. Results and discussion: The final result of this activity, the extension worker is able to provide counseling material that has been made at least 90% of the counseling material.